Structural, Hirshfeld surface and theoretical analysis of two conformational polymorphs of N,N′-bis(pyridin-3-ylmethyl)oxalamide - Jotani, Mukesh M.; Zukerman-Schpector, Julio; Sousa Madureira, Lucas; Poplaukhin, Pavel; Arman, Hadi D.; Miller, Tyler; Tiekink, Edward R. T. * (De Gruyter, 2016)
The common feature of two conformational polymorphs of N,N′-bis(pyridin-3-ylmethyl)oxalamide is their crystallisation in the monoclinic space group P21/c with Z=4. In low symmetry form 1, the central core is effectively planar and the terminal pyridyl rings adopt a syn-periplanar conformation. In the high symmetry form, 2, there are two independent molecules in the asymmetric unit but each is located about a centre of inversion. The rings again are almost perpendicular to the central plane but, from symmetry are anti-periplanar. Computational chemistry shows that symmetric molecules with syn (two-fold) and anti (centrosymmetric) conformations have nearly identical energies. In the molecular packing of each of 1 and 2, supramolecular tapes based on amide-N–H···O(amide) hydrogen bonding are found. In 1, these are connected into layers by C–H···N(pyridyl) interactions, while in 2, the chains are linked into a three-dimensional architecture by C–H···N(pyridyl) interactions. The importance of hydrogen bonding is emphasised in the analysis of the Hirshfeld surfaces.